Extraordinary Presentation of Chronic Pyelonephritis as Retroperitoneal Mass: An Image Report - Mayank Tripathi; Nishant Kumar; Kumar Vineet (Indian Journal of Medical and Paediatric Oncology)
Here we are presenting a unique presentation of chronic pyelonephritis as retroperitoneal mass. It produced a diagnostic dilemma, and final diagnosis was confirmed after histopathology report.